2000
DOI: 10.1203/00006450-200006000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Daily Rhythms in Renal Blood Flow and Urine Production Rate in the Near-Term Sheep Fetus

Abstract: Daily rhythmicity of renal blood flow (RBF) and urine flow (UF) was studied in fetal sheep between 121-125 d of gestation. Fetal arterial blood pressure, heart rate, UF, and right RBF were measured continuously for 24-h periods in 10 sheep. Rhythmic variations during a 24-h period were found for all variables studied. The rhythms of arterial blood pressure and heart rate were highly correlated, whereas an inverse correlation was found between arterial blood pressure with RBF and between arterial blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…This difference may be because the previous study was performed just before full term, at 138 to 140 days gestation, significantly older than in the present study. Consistent with findings in the human fetus (44) and other precocial species such as the sheep (3,4,9,42), in the present study, the majority of control fetal sheep showed clear diurnal cardiac rhythms, with the peak in HR at ϳ2400 and a slightly earlier peak in HRV and MAP. Neither sympathectomy nor vagotomy significantly reduced the magnitude or incidence of these diurnal rhythms, although there was an apparent trend for the peak in HR to be delayed after sympathectomy.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This difference may be because the previous study was performed just before full term, at 138 to 140 days gestation, significantly older than in the present study. Consistent with findings in the human fetus (44) and other precocial species such as the sheep (3,4,9,42), in the present study, the majority of control fetal sheep showed clear diurnal cardiac rhythms, with the peak in HR at ϳ2400 and a slightly earlier peak in HRV and MAP. Neither sympathectomy nor vagotomy significantly reduced the magnitude or incidence of these diurnal rhythms, although there was an apparent trend for the peak in HR to be delayed after sympathectomy.…”
Section: Discussionsupporting
confidence: 77%
“…Diurnal rhythms in fetal HR and HRV are well established in late gestation in the fetal human (44), nonhuman primates (39), and sheep (3,4,9,11,42). These circadian rhythms are thought to be entrained by maternal signals (28) and coordinated, in part, by signals from a fetal "biological clock" in the suprachiasmatic nucleus (SCN) (5,26,41), although other fetal tissues may be involved (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bars represent the time spent on rumination chewing every 10 min near midday and progressive decreased over the next 12 h. The shift of the feeding time to 15.00 h, with the corresponding shift in the RBF circadian profi le, confi rmed the origin of the rhythm. The only work we found reporting a circadian rhythm of RBF in ruminants was performed in near-term ovine foetus (Braaksma et al, 2000). The circadian profi le (acrophase at 01.45 h) was independent of feeding time since the mother was fed ad libitum.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of fetal UPR, data are also conflicting. Diurnal UPR variations measured in catheterized ovine fetuses displayed a maximum at 21 : 30 h and a minimum at 13 : 30 h in a study by Brace and Moore23, but in a study of near‐term sheep fetuses by Braaksma et al 24 urine flow peaked at 07 : 29 h and was lowest at 19 : 00 h. Thus, in view of these conflicting data, measurement time may also be a confounding factor. However, in the present study, we measured fetal bladder volume during a limited period between 10 : 00 h and 17 : 00 h; any diurnal variation would seem to have a minimal effect on our data.…”
Section: Discussionmentioning
confidence: 97%